العلاقات التجارية بين إيالة الجزائر ومملكة الدنمارك في نظر القنصل لودلف هامكين 1746-1751 م. - يوسفي، صرهودة (جامعة وهران 1 أحمد بن بلة - مختبر تاريخ الجزائر, 2020)
يهدف هذا المقال الموسوم بــــ: "العلاقات التجارية بين إيالة الجزائر ومملكة الدنمارك في نظر القنصل لودلف هامكين Ludolf Hammeken. (1746-1751م)" إلى التعريف بأهم ركائز العلاقات التجارية بين الإيالة والمملكة التي تعرض لها لودولف هامكين؛ أول قنصل يمثل الاتحاد الدنماركي النرويجي في إيالة الجزائر؛ الذي عين بعد توقيع معاهدة السلام والصداقة بين الجزائر والدنمارك سنة 1746م، بين داي الجزائر إبراهيم باشا وممثل كرستيان السادس ملك الدنمارك والنرويج، وسنتعرض للموضوع من خلال مجموعة الرسائل الشبيهة بالتقارير حول الإيالة التي بلغت ثمانين رسالة، موجه لغرفة التجارة، وتعرض فيها لعدة نقاط مهمة تخص مداخيل خزينة الإيالة من الهدايا التي تقدمها الدول الأوربية، والهدايا التي يقدمها داي الجزائر لملك الدنمارك، وقد عمل لودولف هامكين على رعاية مصالح مملكة الدنمارك والنرويج في الجزائر، وعقد الصفقات التجارية التي كانت تتم مع الفاعلين الاقتصاديين، وهم حسب تقاريره الداي واليهود الذين كان لهم الأثر الواضح في اقتصاد الإيالة، والقناصل، وبخاصة قنصلي فرنسا والسويد. وللحفاظ على مصالح الدنمارك التجارية في الجزائر قدم القنصل هامكين مجموعة من المقترحات في أكثر من رسالة أهمها: تقديم الهدايا في موعدها المحدد، وتفادي التأخير، كما اقترح منافسة قنصل السويد بتقديم أفضل المنتوجات الدنماركية، وإرسال العتاد الحربي الذي تطلبه سلطة الإيالة، وبالمواصفات التي يطلبها الداي، كما أشار في أكثر من رسالة إلى السلع التي يجب توريدها للجزائر، وقام القنصل بعقد عدة صفقات في الإيالة بالعملة الإسبانية البياستر.
This article, tagged with "Trade relations between the Algerian state and the Kingdom of Denmark in the eyes of Consul Ludolf Hammeken. (1746- 1751) " to introduce the most important pillars of trade relations between the Ayala of Algeria and the Kingdom to which Ludolf Hammeken the first consul representing the Danish Norwegian Union in Algeria, was appointed after the signing of the Treaty of Peace and Friendship between Algeria and Denmark 1746, between Dey of Algeria Ibrahim Pasha, The representative of ChristianVI of Denmark and Norway kingdom, and we will be exposed to the topic through the series of letters similar to reports on the mandate, which amounted to 80 letters addressed to the Chamber of Commerce, in which it presents several important points: the income of the treasury of the Ayala from gifts provided by European countries, and gifts provided by the Dey of Algeria for the King of Denmark, Ludolf Hammeken worked to take care of the interests of the Kingdom of Denmark and Norway in Algeria and to make trade deals with economic actors, namely, The Dey, the Jews who had a clear impact on the economy of the Ayala and consuls, especially the Consuls of France and Sweden. In order to preserve Denmark's commercial interests in Algeria, Consul Hammeken made a series of proposals in more than one letter, the most important of which is: to give gifts on time and avoid delays, as he suggested competing with the Consul of Sweden to provide the best Danish products, and to send the military equipment requested by the Authority, With the specifications requested by The Dey of Algeria, as he pointed out in more than one letter to the goods to be supplied to Algeria, the consul made several transactions in the Spanish currency Of piaster.
Keywords: العلاقات التجارية -- التفاعل الاقتصادى -- الجزائر -- الدانمارك